Research on campus emergency command platform incorporating cloud conferencing technology - ZHU Yue; LIN Chujian (Tongxin xuebao)
The traditional campus emergency command platform faces issues such as limited field acquisition terminals, system incompatibility, insufficient decision-making basis, and poor meeting experiences. By establishing a campus emergency command platform that integrates cloud conferencing technology, new-generation information technologies like cloud computing, 5G, artificial intelligence, and big data were leveraged to integrate conference room systems, security monitoring systems, and cloud video conferencing systems, which had resulted in a platform capable of multi-terminal on-site response, multi-venue access, secure and stable streaming media data transmission, and comprehensive decision-making assistance. It has effectively enhanced emergency response efficiency and facilitated the development of our safe and smart campus initiatives.